A hybrid model of radio frequency biased inductively coupled plasma discharges: description of model and experimental validation in argon. (14th June 2016) - Wen, De-Qi; Liu, Wei; Gao, Fei; Lieberman, M A; Wang, You-Nian
Abstract: A hybrid model, i.e. a global model coupled bidirectionally with a parallel Monte-Carlo collision (MCC) sheath model, is developed to investigate an inductively coupled discharge with a bias source. This hybrid model can self-consistently reveal the interaction between the bulk plasma and the radio frequency (rf) bias sheath. More specifically, the plasma parameters affecting characteristics of rf bias sheath (sheath length and self-bias) are calculated by a global model and the effect of the rf bias sheath on the bulk plasma is determined by the voltage drop of the rf bias sheath. Moreover, specific numbers of ions are tracked in the rf bias sheath and ultimately the ion energy distribution function (IEDF) incident on the bias electrode is obtained. To validate this model, both bulk plasma density and IEDF on the bias electrode in an argon discharge are compared with experimental measurements, and a good agreement is obtained. The advantage of this model is that it can quickly calculate the bulk plasma density and IEDF on the bias electrode, which are of practical interest in industrial plasma processing, and the model could be easily extended to serve for industrial gases.